PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA BELAJAR DI KELAS IV UPT SD NEGERI 005 HANGTUAH KABUPATEN KAMPAR - Febrianti, Mala; Dafit, Febrina (Social Science Academic, 2023)
This study aims to describe the implementation of differentiated learning and the problems of differentiated learning in class IV UPT SD Negeri 005 Hangtuah, Kampar Regency. This research use desciptive qualitative approach. The subjects of this study were class IV teachers, school principals and students at UPT SD Negeri 005 Hangtuah, Kampar Regency. Data collection techniques used are observation, interviews and documentation. The main instrument is the researcher using observation guideline tools, interview guidelines, document review sheets. Data were analyzed through data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses technique and source triangulation. The results showed that class IV teachers at UPT SD Negeri 005 Hangtuah had implemented differentiated learning using 4 differentiated learning components, namely content/material, process, product and learning environment. The problems with implementing differentiated learning at SDN 005 Hangtuah are the teacher's difficulty in determining content/material that interests students so that students are enthusiastic when learning is differentiated and the teacher is still confused about the implementation of process differentiation, because the needs of students vary, but the teacher must be able to treat students according to student needs.